The southeast asian financial crisis: Malaysia rejects economic orthodoxy - Sikorski, Douglas (Penerbit Universiti Kebangsaan Malaysia, 1999)
Pinpointing the actual forces at work in the Asian Financial Crisis, especially politics and other non-market factors that contributed substantially to the loss of confidence, has not been easy. The causes of the crisis might be interpreted as either a failure of Asian capitalism, or alternatively a failure of market capitalism. The first interpretation obviously has a great deal of substance, and Malaysian economic institutions and public policy are not blameless - reckless over-expansion and credit growth, a pegged currency, political imbroglios, etc. Obviously, Malaysia needs to restore confidence in its financial institutions and practices. But Prime Minister Dr Mahathir Mohamad has rejected economic orthodoxy in favour of a more radical strategy. His dramatic gambit has some intellectual legitimacy based on a revisionist movement in economics and may well herald what will be the "new architecture" of the international monetary system